Internet-delivered interventions in mental health rehabilitation: A recovery-oriented online service platform - Ben Itzhak Klutch, Eitan (International Journal of Psychosocial Rehabilitation, 2016)
Objective: The purpose of this article is to present an online service platform applied in Israel, which comprises various technological tools aimed at assisting recovery-oriented psychiatric rehabilitation processes. Method: We describe the technological tools and preliminary results of the e-social and e-occupational programs, developed as part of national initiatives in Israel. Descriptive data, satisfaction evaluation results, survey results of reasons for participation and perceived contributions are presented. Findings: Within e-social programs, peer-led social groups showed high satisfaction rates among clients. Reported contributions included finding friends, emotional, vocational, and self-confidence improvements, acquiring knowledge and helping others. "Safety net" social project has been reported to be beneficial in increasing the sense of security during national emergencies. An e-vocational service for professionals with psychiatric disabilities showed high rates of placement. Conclusions and Implications: Makshivim-Net offers an online assistance for recovery-goals promotion, with preliminary positive results. Rigorous research with standardized measures is needed.